Human Development Index (HDI) of Slum Dwellers in Ichalkaranji (International Journal of Food and Nutritional Sciences, 2022)
The first Human Development Report (HDR) was launched by UNDP in 1990 and since thenbecame a popular, HDI (Human Development Index) has widely used for the assessment of thedevelopment and social well beings. Since its inception (1990), the human development indices provide atool for an assessment of country achievements in different areas of human development. HumanDevelopment Index is a composite index which is very useful for evaluation of the development of eachcountry. The HDI is a measure of achievement in key dimensions of human development: a long andhealthy life, access to knowledge and wisdom and good living. People are real wealth of every nation. Thepurpose of human development is creating conditions in which its people can live a long life and a healthyand productive benefit. The beauty of HDI methodology is that, it can be apply to create comprehensivepicture of peoples human development level and permits comparisons both across countries, regions, andthe world and within countries by ethnic groups, urban and rural locations as well as other key householdand community characteristics. The present study is also based upon versatile UNDP‟s HDI methodology.Concludly, it is found that the status of the human development of the slum dwellers in Ichalkaranji is low.